Information Security Measurement using INDEX KAMI at Metro City - Savitri, Ratna; Firmansyah, Firmansyah; Dworo, Dworo; Hasibuan, Muhammad Said (Bright Publisher, 2024)
Information security is a crucial issue that affects the overall business process, therefore it must be protected and secured. This research was conducted to assess the information security risks at Metro City Communication and Information Office in a structured manner towards information assets in identifying efforts to reduce risks as part of the information security management program. The research method begins with defining the scope, collecting data and supporting documents, evaluating the Information Security Index (KAMI), determining scores in 7 security areas, where strengths/maturity and weaknesses/deficiencies will be identified in each security area. Finally, after obtaining the evaluation results, recommendations will be made. The Information Security Index (KAMI) is a computer-based tool in excel format that can assess and evaluate the completeness and maturity level of information security implementation based on the SNI ISO/IEC 27001 criteria that describe the readiness of the information security framework. The data obtained by the researcher is based on interview results, examination of the availability of Information Security Management System (SMKI) documents, and evidence of SMKI implementation records/archives. The dashboard evaluation results for electronic system category score 17, which is in the high category, governance score is 69, risk management score is 29, framework score is 33, information asset management score is 69, technology score is 81 and supplement score is 0%. Based on verification of the results of the KAMI Index version 4.2 assessment file, a score of 275 was obtained, indicating that information security